Electrical contact resistance between anode and cathode bipolar plates with respect to surface conditions - Kim, Minkook; Lim, Jun Woo; Lee, Dai Gil (ELSEVIER SCI LTD, 2018)
Proton exchange membrane fuel cells (PEMFCs) are one of the most popular alternative power sources for next-generation automobile applications. A bipolar plate is a multifunctional component that performs various roles in the PEMFC stack. Recently, thin (< 200 mu m) bipolar plates made from a continuous carbon fiber reinforced composite (CFRP) have been developed to reduce the mass and cost of the PEMFC stacks. The electrical contact resistance (ECR) between the CFRP bipolar plates is much higher than the ECR between the gas diffusion layer (GDL) and bipolar plate. However, until now, only the ECR between the GDL and bipolar plate has been considered the most important technical target. In this study, the ECR between bipolar plates without bulk resistance were measured to present a standard contact resistance value. The ECR of various types of carbon-based materials for bipolar plate was investigated with respect to hardness and resistivity. A mechanical abrasion method using sandpaper was applied to the surface of CFRPs to remove the resin-rich area and control the surface topology. As a result, the ECR between bipolar plates was quantified with respect to the surface hardness, resistivity and roughness, and optimum surface treatment conditions were obtained to minimize the ECR.
Keywords: MEMBRANE FUEL-CELL; CARBON-BLACK; COMPOSITE; ELECTRODE; PEMFC